Rodrick rules - Bowers, David; Sachs, Gabe; Judah, Jeff; Jacobson, Nina; Simpson, Brad, 1973-; Kinney, Jeff; Gordon, Zachary, 1998-; Bostick, Devon, 1991-; Harris, Rachael, 1968-; Capron, Robert, 1998-; Kranz, Fran, 1983-; Zahn, Steve, 1968-; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2011)
Back in middle school after summer vacation, Greg Heffley and his older brother Rodrick must deal with their parents' misguided attempts to have them bond.
Special features: My summer vacation; audio commentary by director David Brown and author Jeff Kinney; theatrical trailer.
Based upon the second volume of the book series by Jeff Kinney.
DVD release of the 2011 motion picture.
Extras: My summer vacation (shorts): "My magick summer" by Greg Heffley, "My zoo-wee vacation!" by Rowley Jefferson; Audio commentary by director David Bowers and author Jeff Kinney; Theatrical trailer; Sneak peek.
Director of photography, Jack Green ; production designer, Brent Thomas ; film editor, Troy Takaki ; music by Edward Shearmur ; costume designer, Tish Monaghan.
Zachary Gordon, Devon Bostick, Rachael Harris, Robert Capron, Fran Kranz, Steve Zahn, Peyton List, Karan Brar, Grayson Russell, Laine MacNeil.
MPAA rating: PG; for some mild rude humor and mischief.
Keywords: Middle schools -- Juvenile drama; Teenage boys -- Juvenile drama; Friendship -- Juvenile drama; Schools -- Juvenile drama; Diaries -- Juvenile drama; Diaries; Feature films; Children's films; Video recordings for the hearing impaired; Juvenile works; Fiction films -- Juvenile; Film adaptations -- Juvenile; Video recordings for the hearing impaired -- Juvenile; Feature films -- Juvenile; Comedy films -- Juvenile